Observational study of the effect of metaphylaxis treatment on feedlot cattle productivity and health - Maples, William E.; Brorsen, B. Wade; Peel, Derrell; Hicks, Britt (Frontiers in Veterinary Science, 2022)
There is public pressure to reduce antibiotic use in livestock production. Metaphylaxis usage raises special concern as it can lead to healthy animals receiving an unnecessary dose. This paper seeks to determine the impact of metaphylaxis use on cattle productivity and health. Unique data were provided by a commercial feedlot in the Southern Great Plains region of the U.S.A. with an operating capacity greater than 50,000 head. Cattle that received metaphylaxis treatment had substantially poorer health outcomes than those that did not. Propensity score matching was used to estimate the effect of metaphylaxis treatment on feedlot cattle. Cattle were more likely to have been given metaphylaxis treatment if they had a lower weight, were from a sale barn, or had been shipped long distances. Propensity score matching using these three variables is insufficient to identify the effect. The results suggest that the feedlot had information beyond these three items.